2014
DOI: 10.2217/pgs.14.134
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Sult1A1

Abstract: Cytosolic SULT1A1 participates in the bioconversion of a plethora of endogenous and xenobiotic substances. Genetic variation in this important enzyme such as SNPs can vary by ethnicity and have functional consequences on its activity. Most SULT1A1 genetic variability studies have been centered on the SULT1A1*1/2 SNP. Highlighted here are not only this SNP, but other genetic variants associated with SULT1A1 that could modify drug efficacy and xenobiotic metabolism. Some studies have investigated how differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The most common phase II biotransformation enzymes include sulfotransferases (SULTs), N-acetyltransferases (NATs), and methyltransferases (MTs). SULTs utilizes 3′-phospho-5′adenylyl sulfate (PAPS) as a sulfonate donor to catalyze the sulfate conjugation of a wide variety of acceptor molecules that bear a hydroxyl or an amine group (Daniels and Kadlubar, 2014). Sulfonation increases the water solubility of most compounds, and therefore their potential for renal excretion, but it can also result in bioactivation to form active metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The most common phase II biotransformation enzymes include sulfotransferases (SULTs), N-acetyltransferases (NATs), and methyltransferases (MTs). SULTs utilizes 3′-phospho-5′adenylyl sulfate (PAPS) as a sulfonate donor to catalyze the sulfate conjugation of a wide variety of acceptor molecules that bear a hydroxyl or an amine group (Daniels and Kadlubar, 2014). Sulfonation increases the water solubility of most compounds, and therefore their potential for renal excretion, but it can also result in bioactivation to form active metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did see a trend toward lower sulfation clearance in SULT1A1 *2/*2 individuals, this did not reach the statistical significance threshold in the univariate or multivariate analyses. The SULT1A1*2 variant has rarely been studied in the context of drug pharmacokinetics (Daniels and Kadlubar, 2014). Several studies have examined the association of SULT1A1*2 with the pharmacokinetics of tamoxifen and major oxidative metabolites (Jin et al, 2005;Gjerde et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The latter are phase-II detoxification enzymes and have a crucial role in the metabolism of several xenobiotics and endogenous compounds (eg, tamoxifen). 30 , 31 High polymorphism of SULT1A1 has been reported among Caucasian, Chinese, African–American and Korean populations. 32 , 33 Moyer et al reported that the genetic variation in SULT1A1 , including rs750155, which is located in the promoter region (the short arm of chromosome 16) of SULT1A1 , could explain (at least in part) the interindividual variability in the onset of menopause and symptoms before initiation of hormone therapy, and may represent a step towards individualizing decisions for hormone therapy.…”
Section: Discussionmentioning
confidence: 99%